PETF performance indicator: An analysis of current tactical trends in women's tennis - Serfiotis, E. (Coaching and Sport Science Review, 2020)
Many studies have focused on isolated tactical characteristics of tennis and have given less importance to the female game. The goal of this article was to create, based on the existing literature and the observation on the women`s game, the PETF indicator (Pattern success of women 's tennis), which tries to gather the most important tactical needs of the women`s game, and to validate them through questionnaires answered by active players from the WTA circuit and ITF World Tour, seeking to achieve a consensus on the key aspects and analyse their tactical knowledge.